The effect of voting points strategy on developing reading skills and reading comprehension for fifth grade primary students (Journal of the College of Basic Education, 2022)
The current research aims to know (the effect of the voting points strategy on developing reading skills and reading comprehension for fifth grade primary students), and to achieve this, the researcher chose his research community in Baghdad governorate and a sample of fifth grade primary students intentionally from the school (primary knowledge for boys) of the Directorate Raising Baghdad / the third year of the academic year (2018-2019), the research sample reached (52) pupils randomly distributed between two groups, the first is experimental and the number (25) pupils was studied using (voting points strategy), and the other control and the number (27) pupils were studied In the traditional way, the researcher rewarded among the students of (the research sample) in the following variables: (time age calculated by months, academic achievement of parents, Arabic language grades for the past year, and intelligence test), and the researcher formulated (73) a behavioral goal and prepared teaching plans, and chose a subject from the end Reading book; To represent the tools of speed reading test and its validity, and the reading comprehension measurement at the research sample consist of (40) items distributed among five different questions. The tests were characterized by honesty, consistency and objectivity. The researcher applied the three tests of (reading health, speed of reading, and reading comprehension) to the research sample at the end of the experiment, and the researcher used the appropriate statistical means in his research represented (T-test for two independent samples, Kay square, Pearson correlation coefficient, Paragraph difficulty equations and discriminatory force) And the effectiveness of the false alternatives), and the results of the research showed the superiority of the experimental group students over the control group students in (reading health, speed of reading, and reading comprehension) The researcher recommended several recommendations, most notably: Emphasizing the use of (the voting points strategy) that have proven effective in teaching reading to students in the fifth primary grade. The researcher suggested several studies, the most prominent of which is: conducting a similar study for the current research in other dependent variables such as: (motivation, contemplative thinking, and acquisition).